Redox Regulation of Starch Metabolism - Skryhan, Katsiaryna; Gurrieri, Libero; Sparla, Francesca; Trost, Paolo; Blennow, Andreas (Frontiers in Plant Science, 2018)
Metabolism of starch is a major biological integrator of plant growth supporting nocturnal energy dynamics by transitory starch degradation as well as periods of dormancy, re-growth and reproduction by utilization of storage starch. Especially, the extraordinarily well-tuned and coordinated rate of transient starch biosynthesis and degradation suggests the presence of very sophisticated regulatory mechanisms. Together with the circadian clock, land plants (being autotrophic and sessile organisms) need to monitor, sense and recognize the photosynthetic rate, soil mineral availability as well as various abiotic and biotic stress factors. Currently it is widely accepted that post-translational modifications are the main way by which the diel periodic activity of enzymes of transient starch metabolism are regulated. Among these mechanisms, thiol-based redox regulation is suggested to be of fundamental importance and in chloroplasts, thioredoxins (Trx) are tightly linked up to photosynthesis and mediate light/dark regulation of metabolism. Also, light independent NADP-thioredoxin reductase C (NTRC) plays a major role in reactive oxygen species scavenging. Moreover, Trx and NTRC systems are interconnected at several levels and strongly influence each other. Most enzymes involved in starch metabolism are demonstrated to be redox-sensitive in vitro. However, to what extent their redox sensitivity is physiologically relevant in synchronizing starch metabolism with photosynthesis, heterotrophic energy demands and oxidative protection is still unclear. For example, many hydrolases are activated under reducing (light) conditions and the strict separation between light and dark metabolic pathways is now challenged by data suggesting degradation of starch during the light period.